2017
DOI: 10.1002/2016jd026363
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and biogeochemical importance of high‐latitude dust in the Arctic and Southern Ocean‐Antarctic regions

Abstract: Recent studies suggest that around 5% of global dust emissions come from sources in the high latitudes (≥50°N and ≥40°S). A substantial proportion of this dust remains within the high latitudes and is deposited in marine and terrestrial environments. Stable air masses and limited atmospheric convection associated with cold climates reduce vertical mixing of dust plumes and can restrict the altitudes at which the deposition of dust originating from high latitudes can take place. Within local high‐latitude syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 23 publications
5
31
0
Order By: Relevance
“…In general, aerosol dust and iron concentrations peak closest to the coastlines and during summer. Emissions of dust from > 50 • N are ∼ 1.3 ± 0.2 % of the global dust total, which is half of the estimates derived from field and satellite data at 2 %-3 % of the global total (Bullard, 2017;Bullard et al, 2016). However, the resulting magnitude and seasonality of dust concentrations have been shown in a recent study to be consistent with observed measurements from Svalbard (Tobo et al, 2019).…”
Section: High-latitude Dust and Iron Aerosolsupporting
confidence: 75%
See 2 more Smart Citations
“…In general, aerosol dust and iron concentrations peak closest to the coastlines and during summer. Emissions of dust from > 50 • N are ∼ 1.3 ± 0.2 % of the global dust total, which is half of the estimates derived from field and satellite data at 2 %-3 % of the global total (Bullard, 2017;Bullard et al, 2016). However, the resulting magnitude and seasonality of dust concentrations have been shown in a recent study to be consistent with observed measurements from Svalbard (Tobo et al, 2019).…”
Section: High-latitude Dust and Iron Aerosolsupporting
confidence: 75%
“…2) from the AERONET observational datasets (Holben et al, 1998), as subsampled in Albani et al (2014), shows good agreement globally (correlation: r 2 = 0.64). This results in MAM annual global mean emissions of 3250 ± 77 Tg dust a −1 (Aitken 16 Tg a −1 , accumulation 36 Tg a −1 , coarse 3198 Tg a −1 ), which is at the higher end of literature estimates of ∼ 500-4000 Tg dust a −1 (Bullard et al, 2016;Huneeus et al, 2011;Kok et al, 2017). Dust emissions in MAM are 84 ± 4 % higher than our previous mean of 1768 Tg dust a −1 in BAM (Scanza et al, 2018) because dust lifetime has proportionally decreased (Table S2), which affects coarse-mode dust aerosol (wherein 98 %-99 % of total dust mass is emitted) more than fine-mode dust aerosol.…”
Section: Global Dust Comparisonsmentioning
confidence: 87%
See 1 more Smart Citation
“…Although the potential influence of dust input is acknowledged not much is known from dust input in the Arctic Ocean (Bullard, 2017). In Transect 3 we did see increased DFe in the surface at Station 147 (Figures 4D, 7).…”
Section: Surface and Shelfmentioning
confidence: 88%
“…For instance, dust storms have been recorded on susceptible soils in mid‐latitude regions such as Germany (Deetz et al, ) and Ukraine (Birmili et al, ), and on glacial outwash plains in Alaska, United States (Crusius et al, ), Iceland (Dagsson‐Waldhauserova, Arnalds, and Olafsson, ), and New Zealand (Marx and McGowan, ). Indeed, recent studies suggest that some five per cent of global soil dust emissions come from sources in the high latitudes (Bullard, ), and some of these sources are not detected in global satellite surveys such as Prospero et al () and Washington et al (), which used the Total Ozone Monitoring Spectrometer or the more contemporary Moderate Resolution Imaging Spectroradiometer employed by Ginoux et al ().…”
Section: Dust Storm Sources and Transport Pathwaysmentioning
confidence: 99%